2011
DOI: 10.1016/j.bone.2011.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of bone loss with ultrasound induced dynamic mechanical signals in an OVX induced rat model of osteopenia

Abstract: This study tests the hypothesis that an ultrasound generated dynamic mechanical signal can attenuate bone loss in an estrogen deficient model of osteopenia. Eighty-four, sixteen week old Sprague-Dawley rats were divided into six groups: baseline control, age-matched control, ovariectomy (OVX) OVX control, OVX + 5 mW/cm 2 ultrasound (US), OVX + 30 mW/cm 2 US and OVX + 100 mW/cm 2 US. Low intensity pulsed ultrasound (LIPUS) was delivered transdermally at the L4/L5 vertebrae, using gelcoupled plane wave US transd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 44 publications
4
26
0
Order By: Relevance
“…Thus, we examined the trabecular micro-architecture using micro-CT scanning after the administration of gastrodin. Previous micro-CT analysis has shown that normal trabecular bone micro-architecture dramatically deteriorates after ovariectomy [59], which is consistent with the results obtained in our research. In addition, ovariectomy could induce osteoclast formation by TRAP staining in vivo.…”
Section: Discussionsupporting
confidence: 96%
“…Thus, we examined the trabecular micro-architecture using micro-CT scanning after the administration of gastrodin. Previous micro-CT analysis has shown that normal trabecular bone micro-architecture dramatically deteriorates after ovariectomy [59], which is consistent with the results obtained in our research. In addition, ovariectomy could induce osteoclast formation by TRAP staining in vivo.…”
Section: Discussionsupporting
confidence: 96%
“…The overall lack of trabecular bone alteration led to significant preservation of specific bone surface (BS/BV) in the Low20 group compared with the Obtx sham group. Interestingly, the Low20 average intensity was the lowest among all the treatment groups (see Table 1) and closely approached the average intensity used by Ferreri et al (2011) in the LIPUS treatment of osteopenic rat vertebrae (0.1 mW/cm 2 ). The LIPUS transducer used in that study was flat, with the aperture much larger than rat vertebrae, so that the surrounding muscle was likely affected as well.…”
Section: Discussionmentioning
confidence: 52%
“…LIPUS intensity of 100 mW/cm 2 was found to be the minimum intensity that mitigated bone loss in osteopenic animals (Ferreri et al 2011).…”
mentioning
confidence: 89%
See 2 more Smart Citations